Use of sulforaphane in COVID-19: Clinical trials are needed. (May 2022) - Kow, Chia Siang; Ramachandram, Dinesh Sangarran; Hasan, Syed Shahzad
Abstract: We read with interest the narrative review authored by Kiser et al. (2021), which discussed extensively the antioxidant effect and anti-inflammatory effect of sulforaphane, a dietary supplement found in high amounts in cruciferous vegetables that ais orally accessible and well-tolerated. Notably, in their review, the authors also discussed the potential use of sulforaphane in patients with coronavirus disease 2019 (COVID-19). Sulforaphane mediates the inhibitory effect on NLRP3 inflammasome activation and we believe that this could be the main mechanism where sulforaphane is useful for patients with COVID-19.